Hypertension and associated risk factors in individuals infected with HIV on antiretroviral therapy at an urban HIV clinic in Uganda - Aggrey S Semeere, MMed MAS; Joseph Sempa, MSc; Issac Lwanga, MMed; Rosalind Parkes-Ratanshi, MRCP PhD; Andrew Kambugu, MMed (The Lancet Global Health, 2014)
Background: Scale-up of antiretroviral therapy (ART) might precipitate an increase in non-communicable diseases (NCDs) in adults infected with HIV in sub-Saharan Africa based on data from resource-rich settings. Hypertension is a major modifiable risk factor for cerebrovascular and cardiovascular NCDs. We estimated prevalence, incidence, and risk factors for incident hypertension in adults infected with HIV on ART at an urban clinic in Uganda. Methods: From a cohort of adults infected with HIV (>18 years) who initiated ART between Jan 1, 2005, and Jan 3, 2012, at the Infectious Diseases Institute clinic in Kampala, we report the prevalence, incidence, and cumulative incidence (with death as a competing risk) of hypertension (≥140/90 mm Hg). Risk factors for hypertension were evaluated with Cox proportional hazards regression. Findings: Of 9806 individuals who initiated ART, 6351 (64·8%) were women, median age was 36 years (IQR 31–42), and median follow-up was 3·9 years (2·2–5·9). Overall prevalence of hypertension was 15·1% (1472 individuals); older individuals (>50 years) had higher prevalence (299, 38·6%). By year 1, cumulative incidence was 1% and by year 5, it was 3·6%. Overall incidence was 19 cases per 1000 person-years. Multivariate regression showed male sex, older age, increasing body-mass index, and use of stavudine at initiation was associated with an increased rate of hypertension. Interpretation: Of our patients, we noted a prevalence of hypertension between 14·6% and 28·5%, similar to the general Ugandan population. Besides traditional risk factors for hypertension, use of stavudine was also identified. Awareness of NCD comorbidity and AIDS-associated risk factors are increasingly important for clinicians caring for adults on ART in sub-Saharan Africa. Funding: University of California Global Health Institute (UCGHI) supported GloCal Fellowship funded by the Fogarty International Center (FIC) at the National Institutes of Health (NIH) R25TW009343.